ANALYSIS OF RAINFALL AND TEMPERATURE EFFECTS ON YAM YIELD IN THE KRACHI EAST DISTRICT OF GHANA - Magna, E. K.; Ofori, B. D.; Ojo, S. (UDS International Journal of Development, 2018)
The study determined the relationship between selected climatic parameters and yam yield in the Savannah-transitional zone of Ghana. The study used descriptive and multiple linear regression analysis to analyse meteorological data (i.e. temperature and rainfall) from the Ghana Meteorological Service (GMA) and the yam yield data from the Ministry of Agriculture (MoFA) from 2005-2015. The Pearson product-moment correlation showed a weak negative and positive relationship for rainfall, temperature and yam yield. A multiple linear regression analysis for rainfall (X2), temperature (X1) and yam yield (Y) was derived as: Y=11.243+0.204X_1-0.002X_2. It therefore discovered that only 10.6% of the proportion of variation of yam yield was explained by rainfall and temperature during the period of study. 89.4 % of the yam yield as explained by the model was probably due to exogenous (external) factors. The research showed that climatic variables (i.e. rainfall and temperature) have little influence on yam yield in the Krachi East District during the period of study. In conclusion government should introduce new improved yam breeding programmes/technology, employ modern farming tools and avail farming inputs/credit facilities to farmers to expand and enhance their eï¬ƒciency in yam production to ensure proï¬tability of yam sales. Keywords: Temperature, Rainfall, Yam, model, Dambai, Crop production